Between solidarity and the conflict of generations. Intergenerational relations in biographical narratives - Słaboń, Andrzej (Journal of Public Governance, 2019)
Objectives: The purpose of this text is to identify the main types of intergenerational relationships and methods of integration different generations applied in everyday life. Recognition of these practices should be used in inclusion policy. Research Design & Methods: This article uses qualitative methods of sociology, in particular biographical narratives (story of life) to explore types of intergenerational relationships. Findings: This paper finds that relational structures are an important part of every biographical narrative. Research has identified five types of intergenerational relationships. Implications / Recommendations: This article stresses the importance of biographical work and the restrictions on the creation of multigenerational groups as a fairly common way of integrating different generations. Contribution / Value Added: The approach presented in this article opens new possibilities for a policy of inclusion and ways of counteracting intergenerational conflicts.